Mapping Researches of Green Sukuk: A Bibliometric Approach - Fauza, Nurlia; Suryomurti, Wiku (Universitas Islam Negeri Alauddin Makassar, 2024)
This study highlights the current state of green sukuk research, conducted through journals filled with descriptions of digital objects. This analysis focuses on the character and writing style of keywords, authors, and journals. The data analyzed amounted to 123 studies published in Dimensions (https:// dimension.ai). Descriptive statistical methods were used, and bibliometric analysis was performed using R Biblioshiny to determine bibliometric maps. The number of articles discussing the green sukuk theme has been quite large in recent years. Many journals have published articles on green sukuk, most of which is the Journal of Islamic Accounting and Business Research which contains several authors who investigate the topic with various keywords, the most prolific author is Musari K., and the most widely used keyword is